2020
DOI: 10.1259/bjr.20200571
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric prostate MRI-based intensity-modulated radiation therapy guided by prostatic calcifications

Abstract: Objectives: The optimal technique to administer image-guided radiation therapy for prostate cancer remains poorly defined. This study assessed outcomes after multiparametric prostate MRI-based planning was delivered with image-guided radiation therapy using prostatic calculi observed on cone beam CT (CBCT). Methods: Between January 2015 and December 2017, 94 consecutive patients were treated with CBCT-based image-guided radiation therapy (IGRT) without fiducial markers. MRI was routinely incorporated for targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Prostate cancer is one of the most frequently diagnosed malignancies among men worldwide, and prostate microcalcification has garnered attention as a potential prognostic marker for bone metastasis in this disease [11]. Previous research has indicated that while it often arises as a consequence of scar tissue formation following prostatitis resolution, several factors, including chronic prostatitis, prostatic urine retention, prostatic duct stenosis, abnormalities in calcium and phosphorus metabolism, and psychosocial factors, may contribute to its development [12][13][14]. Epidemiological studies have also linked poor dietary habits (such as irregular breakfasts and consumption of fatty snacks), alcohol consumption, and certain work-related habits (like prolonged sitting, late-night work, and the habit of holding in urine) to an increased risk of calcification [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Prostate cancer is one of the most frequently diagnosed malignancies among men worldwide, and prostate microcalcification has garnered attention as a potential prognostic marker for bone metastasis in this disease [11]. Previous research has indicated that while it often arises as a consequence of scar tissue formation following prostatitis resolution, several factors, including chronic prostatitis, prostatic urine retention, prostatic duct stenosis, abnormalities in calcium and phosphorus metabolism, and psychosocial factors, may contribute to its development [12][13][14]. Epidemiological studies have also linked poor dietary habits (such as irregular breakfasts and consumption of fatty snacks), alcohol consumption, and certain work-related habits (like prolonged sitting, late-night work, and the habit of holding in urine) to an increased risk of calcification [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…However, MRI only workflows are sought for because of the superior soft tissue contrast of MRI compared with CT and because they eliminate the risk for MR-CT registration errors as well as reduce the exposure of patients to ionizing radiation. [209][210][211] Conventional MRI workflows using magnitude data lack the ability to differentiate between diamagnetic calcification that are a common finding in the prostate, 212 fiducial markers such as gold fiducial markers that are more diamagnetic than calcification or titanium encapsuled seeds that are strongly paramagnetic, and blood products that possess a paramagnetic susceptibility. Therefore, the risk for error might outweigh the benefits of an MRI-only workflow.…”
Section: Musculoskeletal and Spinal Applicationsmentioning
confidence: 99%
“…Therefore, the risk for error might outweigh the benefits of an MRI‐only workflow 209 . Moreover, the use of prostatic calcification as an internal fiducial marker has been proposed 210 …”
Section: Organ Specific Considerationsmentioning
confidence: 99%
See 1 more Smart Citation